2006
DOI: 10.1080/10473289.2006.10464577
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Calcium Carbonate Content and Emission Characteristics of Incense

Abstract: In Taiwan and China, calcium carbonate is commonly added as a filler during incense production to lower the cost. This study has found an unexpected benefit for this practice: it reduces particulate emission. Nine types of the popular incense on the local market were chosen for this study. The calcium content in raw material incense was analyzed by inductively coupled plasma atomic emission spectrometry, followed by X-ray diffraction (XRD) spectroscopy. The correlation between the calcium content and emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
2
5
1
Order By: Relevance
“…These results indicate that the addition of nano-CaCO 3 significantly reduces the burning time. For the burning rate, results similar to those obtained in our previous study, which investigated nine types of incense and found that incense with higher nano-CaCO 3 content had higher burning rates, were obtained (Yang et al, 2006). In this study, we controlled the process variations and added accurate amounts of nano-CaCO 3 to help verify the reduction of burning time.…”
Section: Burning Time and Burning Rate Of Test Incensesupporting
confidence: 72%
See 1 more Smart Citation
“…These results indicate that the addition of nano-CaCO 3 significantly reduces the burning time. For the burning rate, results similar to those obtained in our previous study, which investigated nine types of incense and found that incense with higher nano-CaCO 3 content had higher burning rates, were obtained (Yang et al, 2006). In this study, we controlled the process variations and added accurate amounts of nano-CaCO 3 to help verify the reduction of burning time.…”
Section: Burning Time and Burning Rate Of Test Incensesupporting
confidence: 72%
“…Dynamic mechanical thermal analysis showed that the addition of nano-CaCO 3 led to an increase in storage modulus and glass transition temperature for both PVC and PVC/Blendex blend (Chen et al, 2004). We investigated nine types of incense and found that incense with higher CaCO 3 content had lower PM and PAH emissions (Yang et al, 2006). Therefore, the incense used in the present study was made in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CaCO 3 with refractory characteristics in terms of low heat transfer coefficient (0.05 W/mol·k) and high molar heat capacity (81.88 J/mol·K) will prevent air convection and thus raise the burning rate of inflammable substances. Compared with the result conducted by Yang (Yang et al, 2006), the reasons for high burning rate observed in this study included different raw materials, smaller diameter incense (2.2 mm in this study, 2.5-3.0 mm in previous study), incense density changes resulted from incense production (semi-handmade in this study, machine-made in previous study).…”
Section: Burning Time and Burning Rate Of Test Incensecontrasting
confidence: 65%
“…2 (Yang et al, 2006). The air exchange rate (Ach) in a domestic environment in Taiwan ranges from 0.8 to 3.5 Ach in summer and 0.5 to 2.0 Ach in winter (Li and Ro, 2000).…”
Section: Sampling Programmentioning
confidence: 99%
See 1 more Smart Citation